Comprehensive organic functional group transformations II - Katritzky, Alan R.; Taylor, Richard J. K. (Elsevier, 2005)
Comprehensive Organic Functional Group Transformations II (COFGT-II), designed for specialist and nonspecialist chemists, active in academic, industrial, and government laboratories, now updates the developments of functional group transformations since the publication of the COFGT 1995. COFGT-II is structured in precisely the same manner as the original COFGT work, allowing comprehensive coverage of all organic functional group transformations.
Keywords: Organic compounds -- Synthesis.; elektronické knihy; electronic books